Rapunzel - Gibb, Sarah; Grimm, Wilhelm, 1786-1859.; Grimm, Jacob, 1785-1863. (Chicago : Albert Whitman, 2011)
A retelling of the German folktale in which a beautiful girl with long golden hair is kept imprisoned in a lonely tower by a witch.
aOriginally published: London : HarperCollins Children's, 2010.
Keywords: Folklore -- Germany; Fairy tales